Surgical Repositioning and Adjunctive Injectable Platelet-rich Fibrin for Severe Intrusive Luxation of Permanent Maxillary Incisors: A One-year Follow-up Case Report - V Jeevitha; S Manoj; Pooja Prabhu; R Vaishnavi; Cherry Biyani (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Intrusive Luxation (IL) is one of the most severe forms of traumatic dental injuries, causing extensive damage to the Periodontal Ligament (PDL), pulp, and supporting alveolar bone. Management of severe intrusion in mature permanent teeth remains challenging because of complications such as pulp necrosis, inflammatory root resorption, replacement resorption, and ankylosis. Injectable Platelet-Rich Fibrin (I-PRF), an autologous platelet concentrate, has gained attention because of its regenerative potential and ability to promote soft and hard-tissue healing. The present case report describes the multidisciplinary management of severe traumatic intrusion of the maxillary incisors in a 36-year-old male patient following an accidental fall. Clinical and radiographic examination revealed severe intrusion (>7 mm) of teeth 12 and 21, accompanied by uncomplicated crown fractures and subluxation of tooth 11. Owing to the severity of intrusion and complete root development, immediate surgical repositioning was performed and stabilised using a flexible fibre splint. Root canal treatment was initiated one week after surgical repositioning as a preventive (prophylactic) intervention in accordance with the International Association of Dental Traumatology (IADT) 2020 guidelines for mature intruded teeth, owing to the high-risk of pulp necrosis and inflammatory external root resorption. Calcium hydroxide was used as an intracanal medicament. To enhance periodontal healing and PDL regeneration, freshly prepared I-PRF was aspirated immediately after centrifugation into a sterile syringe and slowly administered through the gingival sulcus surrounding the affected teeth under aseptic conditions using 30 Gauge needle. The injections were performed once weekly for four consecutive weeks. At the one-year follow-up, clinical and radiographic evaluation demonstrated satisfactory periodontal and periapical healing without evidence of root resorption or ankylosis. The patient remained asymptomatic with satisfactory functional and aesthetic outcomes. This case highlights the potential role of I-PRF as an adjunctive regenerative therapy in the management of severe IL.